Consensus on Postoperative Recommendations After Transsphenoidal Surgery - Knappe, Ulrich J.; Moskopp, Dag; Gerlach, Rüdiger; Conrad, Jens; Flitsch, Jörg; Honegger, Jürgen B. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Guidelines for patient behavior following transsphenoidal surgery do not exist. To gain generally recommendations, the German pituitary working group conducted a study among pituitary surgeons to elucidate their opinions and customs of patients’ counselling.Methods Questions concerning daily activities, exertion of sports and work life were addressed. It was asked to provide the postoperative time interval after which specific activities can be resumed both after a routine or an extended approach.Results Fourteen pituitary surgeons returned the completed questionnaire. Following routine operations, washing the hair was allowed within one week, blowing the nose after 3, flying on an airplane and driving a car after one, lifting heavy weights after 4, playing wind instruments after 6, use of CPAP (continuous positive airway pressure) device after 3, permit leisure sports after 2 to 4 weeks (except for scuba diving). Competitive sports can be resumed after 6 weeks. Occupation with mental demands was considered feasible after 2 weeks, with physical labor after 4 weeks. After extended transsphenoidal surgery, the recommended time interval was roughly twice as long compared to the routine approach. Driving a car was allowed within the first 4 weeks after surgery by some pituitary surgeons, while others allow driving only after 3 months analogous to the regulations after craniotomy. The risk of scuba diving was considered high.Conclusions The data of our study and the literature, and expert opinions from related scientific fields resulted in a consensus on recommendations for patients’ conduct to minimize risks after transsphenoidal surgery.
Keywords: pituitary tumor; transsphenoidal surgery; postoperative recommendations